Study of η-einstein soliton on α-sasakian manifold admitting schouten-van kampen connection - Abhijit Mandal; Meghlal Mallik; Rima Das; Gopan Saha; Enamul Hoque; Md Rejuan (Journal of Hyperstructures)
The purpose of the present paper is to study some properties of α -Sasakian manifolds with respect to Schouten-van Kampen connection. We study η-Einstein soliton on pseudo-projectively flat α-Sasakian manifolds with respect to Schouten-van Kampen connection. Further, we discuss η-Einstein soliton on quasi-concircularly flat and Wi-flat α-Sasakian manifolds with respect to this connection.